Analisis Faktor-faktor Profitabilitas Bank - Khaerunisa Harsono (Jurnal Maksipreneur, 2021)
The purpose of this research is to examine the effect of the minimum capital adequacy ratio, the ratio of non-performing loans, operating costs and operating income, and company size on profitability. This research was conducted in the banking industry listed on the Indonesia Stock Exchange from 2015 to 2019. This research was conducted in the banking industry listed on the Indonesia Stock Exchange (BEI). This study used a purposive sampling method in determining the research sample. The results of this study found that the capital adequacy ratio, operating expenses and operating income (BOPO) of the bank, and Non-performing loan ratio had a significant effect on profitability. On the other hand, company size has no significant effect on the profitability of banks listed on the Indonesia Stock Exchange for the period 2015-2019.